PENGARUH MANAJEMEN RANTAI PASOK BERBASIS SISTEM ERP DALAM MENINGKATKAN KINERJA PT UNILEVER - Rivaldo, Januryanto; Wenny; Danielson; Hutagaol, Sherina (Transpublika Publisher, 2022)
Supply chain management is an efficient method for preserving a company's competitive advantage and maximizing its production. ERP systems, in relation with Supply Chain Management, are useful tools for enhancing organizational performance and preserving competitive advantage. ERP systems are concerned with enhancing work operations and data utilization. This study aims to determine how ERP systems can assist distribution organizations in enhancing their supply chain management. This is a literature review that collects data from a variety of textbooks, scholarly articles, and credible information from companies and other reputable sources. The findings revealed that adopting a supply chain management system in order to become such a digital corporation involves and connects the entire company, outside of marketing, to the digital and physical worlds of consumers, and synchronizes activities across the organization. Unilever used real-time digital enterprises successfully to unleash value and facilitate corporate growth.